An in vitro evaluation of antimicrobial activity of five herbal extracts and comparison of their activity with 2.5% sodium hypochlorite against Enterococcus faecalis - Divya Saxena; Suparna Ganguly Saha; Mainak Kanti Saha; Sandeep Dubey; Margie Khatri (Wolters Kluwer Medknow Publications, 2015)
Context: Sodium hypochlorite is the most widely used irrigant in endodontic practice, but it has various disadvantages. Literature has shown that herbal products such as Propolis, Azadirachta indica (AI), Triphala, Curcuma longa, and Morinda citrifolia (MC) possess good antimicrobial properties and thus can be used as potential endodontic irrigants. Aim: To evaluate and compare the antimicrobial activity of five herbal extracts, i.e., Propolis, AI, Triphala, C. longa, and MC with that of 2.5% sodium hypochlorite against Enterococcus faecalis. Materials and Methods: E. faecalis American Type Culture Collection 21292 was inoculated onto brain heart infusion agar plate. Discs impregnated with herbal medicaments were placed on the inoculated plates and incubated at 37°C aerobically for 24 h and growth inhibition zones were measured. Statistical Analysis: Mean zone of inhibition in descending order was found as sodium hypochlorite > Propolis > AI > Triphala > C. longa = MC > ethanol. Statistical analysis was performed using one-way analysis of variance which showed a significant difference in the zone of inhibition of sodium hypochlorite and Propolis (P < 0.001). Results: Propolis showed highest zone of inhibition among all the herbal extracts next to sodium hypochlorite. Conclusion: Propolis and AI have significant antimicrobial activity against E. faecalis.